ANALYSIS OF SYSTEMIC LIQUIDITY RISK FOR THE BANKING SECTOR IN BOSNIA AND HERZEGOVINA (BH) - Almir Alihodžić; Hye-jin Cho (Ekonomski Vjesnik, 2015)
The purpose of this paper is to relate the Danish concept of the “Balance Principle” to test the hypotheses of systemic liquidity risk in the banking sector. In the paper, the major econometric method is to gauge the general applicability of theories of liquidity and to test the applicable validity of Bosnia and Herzegovina (BH). A prime example for this study is taken from the first quarter of 2004 to the second quarter of 2014. Our intention here is to consider the identification of macroeconomic parameters that positively affect the growth of the banking sector. The parameter liquidity, i.e. liquid assets / total assets will be observed as a dependent variable, and nonperforming loans / total loans, average profitability on equity capital, non-interest expenses / total revenue, the average required reserve, total loans, the money supply in the wider sense, net capital / risk weighted assets and net performing assets / total assets will be used as independent variables. The purpose of the paper is to determine whether there is interdependence in the movement between the independent and dependent variables through a multiple linear regression.